Smart Bracelet for Tracking the Location of Dementia Patients - Dewi, Ervin Masita; Nurmajid, Ikhsan Malik; Putro, Trisno Yuwono; Kirana, Nurista Wahyu; Saefudin, Didin (Jurnal Rekayasa Elektrika, 2024)
The rising number of dementia patients worldwide is a significant concern. Dementia, marked by deteriorating memory, language, problem-solving abilities, and other cognitive skills, affects millions globally. According to the World Health Organization (WHO), over 55 million people currently live with dementia. Dementia's impact on patients, their families, and healthcare systems is substantial. Patients often need continuous supervision and care, posing challenges for caregivers. Wandering is a frequent issue among dementia patients, leading to safety risks and a high chance of getting lost. Innovative technological solutions, such as portable monitoring devices, are crucial in tackling these issues. A smart bracelet with Global Positioning System (GPS) can be vital for ensuring dementia patients' safety. These devices provide real-time location tracking, giving caregivers and family members peace of mind by enabling them to quickly locate patients who wander off. This makes the bracelet highly effective for monitoring dementia patients' locations, as it will send notifications to a messenger application on a smartphone with a link to the patient's location if they move beyond a 20-meter radius from home. The bracelet uses GPS for distance and location tracking. The patient's location is pinpointed by the intersection of latitude and longitude coordinates. The device has a minimal margin of error, with a latitude error of 0.003% and a longitude error of 0.008%.